Visualization of Aerological Diagram and Analysis of Atmospheric Sounding Information Using Raob with Model Data During Low Visibility Conditions at Cengkareng Meteorological Station - Bagus Primohadi Syahputra; Muhammad Yusuf; Yosafat Donni Haryanto; Nelly Florida (Universitas Serambi Mekkah, 2022)
The limitations of in-situ observations of the upper air are one of the obstacles in analyzing the weather. The use of data models can be one solution. The purpose of this study was to determine the accuracy of the data model in providing upper air information using RAOB as a visualization tool for aerological diagrams and sounding information analyzers. The data used are radiosonde observation data from the Cengkareng meteorological station and 1000 – 100 mb ECMWF pressure level models at the same location as the in-situ observations. The time chosen is when the haze and mist occur at the observation time 00 UTC for 5 events each. The method used is pearson correlation and simple visual verification. The results obtained that the correlation of the significant point plot data diagram when the mist occurs is 0.76 and when the haze occurs is 0.67 and visually as a whole show that the model data is quite close to the observation data. Correlation of 59 sounding information as a whole produces a value of 0.85 – 0.99 when the Mist occurs and a value of 0.89 – 0.99 when the Haze occurs. It is hoped that these results can be used as a consideration for the use of data models in filling in the gaps in radiosonde observation data. Keywords: Sounding Information, RAOB, Radiosonde, ECMWF Models